Designing Creative Learning in Maharah Kitabah: Narrative Inquiry on Lecturers Experiences - Arifa, Zakiyah; Al Faruq, Umar; Fatim, Al Lastu Nurul; Editia , Qushayyi Akbar; Malmous, Anas (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2026)
This study highlights the significance of creative learning design in Maharah Kitabah (Arabic writing skills) as an essential pedagogical approach in higher education. This research aims to explore how Arabic lecturers conceptualize and implement creative instructional designs that foster reflective, adaptive, and outcome-based learning. By employing a qualitative narrative inquiry, data were collected through written narratives, in-depth interviews, and document analysis involving four lecturers from different Islamic universities in East Java, Indonesia. The participants were selected based on their teaching experience in Maharah Kitabah, involvement in innovative instruction, and familiarity with project-based learning. The study prioritizes depth of data through multiple sources of evidence. To ensure credibility, the triangulation and member checking were carried out. The findings reveal that all lecturers shared a similar pedagogical vision-learner-centered learning integrated with Outcome-Based Education (OBE), a balanced emphasis on theory and practice, meaningful use of digital technologies, and flexible curriculum design. Despite these commonalities, variations emerged in focus and strategies: process writing and publication, project-based learning, hybrid manual-digital approaches, and digital portfolios. These creative designs demonstrate pedagogical innovation aligned with 21st-century learning demands by encouraging learner autonomy, critical thinking, and reflective engagement. However, the study acknowledges limitations in participant scope and contextual generalization. Overall, this study contributes theoretically and practically to the development of creative, humanistic, and sustainable Arabic language learning models in higher education by recommending learner-centered and project-based writing models, reflective portfolio assessment, and the integration of digital platforms to support collaborative writing, feedback, and publication in Maharah Kitabah.